Kerangka Regulasi Open Banking Dan Perlindungan Data Pribadi Nasabah - Fitrianto, Bambang; Gaja, Armilati Suryani Putri; Dalimunthe, Aldi Fadillah; Manurung, Anggreyny Vini R Br; Harahap, Aina Sari (Sharia Journal and Education Center Publishing, 2026)
This research study investigates and analyzes the intersection of accelerated digitalization in the banking industry through the Open Banking model with the fundamental need to protect personal data. In the digital economy, open data access through Application Programming Interfaces (APIs) serves as a driver of financial innovation, but also increases risks to customer privacy. This study analyzes how existing regulatory tools address changes in data exchange between platforms to ensure that operational efficiency does not compromise the right to personal data. The purpose of this research study is to discuss legal norms related to the management of open banking and legal protection mechanisms for customers as data owners. This analysis focuses on the alignment of regulations with the financial services regulatory sector through the currently implemented personal data protection law. This analysis will provide a comprehensive discussion emphasizing the comprehensiveness of regulations on open banking, the appropriateness of legal forms of protection provided to bank customers, and the legal norms related to the management of open banking and legal protection mechanisms for customers as data owners. Furthermore, this study is useful in providing policy advice to financial authorities in formulating technical cybersecurity standards to reduce the possibility of misuse of customer data in the digital environment.